Cold Compress to Reduce Pain During Invasive Procedures: Systematic Review - Samran, Samran; Esti Mulyawanti; Alverdo Yusufa; Syahrir Aprizal; Titin Suhaeni; Dhea Natashia (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2025)
Pain is one of the common effects experienced by children during invasive procedures, such as infusion, injection, blood sampling, and others. Cold compresses are a non-pharmacological method believed to be effective in reducing pain in children prior to invasive procedures. The purpose this systematic review aims to evaluate the effectiveness of cold compresses in reducing pain in children during invasive procedures. The study adopts a systematic review approach following the PRISMA guidelines. The synthesized articles were selected based on Randomized Controlled Trials (RCT) designs and met the inclusion criteria, namely children aged 0–18 years undergoing invasive procedures. Articles were sourced from PubMed, Cochrane, and ProQuest. The collected data included population, intervention, comparison, and outcomes measured using the Visual Analog Scale (VAS) and FLACC. A review of three articles showed that cold compresses significantly reduced pain intensity in children before invasive procedures. Data analysis using a random-effects model of secondary trial data revealed a mean difference in pain intensity of 0.34 (95% confidence interval: [-0.76, -0.33]), assessed using VAS and FLACC scores. Cold compresses are proven effective in reducing pain intensity in children before invasive procedures. Further studies are needed to explore the influence of other variables, such as the type of procedure and the duration of application